2016 Wireless Telecommunications Symposium (WTS) 2016
DOI: 10.1109/wts.2016.7482026
|View full text |Cite
|
Sign up to set email alerts
|

Congestion-aware RPL for 6L0WPAN networks

Abstract: Abstract-IPv6 over low power wireless personal area network (6LoWPAN) is promising to be used in many different IoT applications. Recently, many protocols have been proposed for 6LoWPAN networks such as RPL routing protocol which is developed by the ROLL working group and expected to be the standard routing protocol for 6LoWPAN. Many problems are facing 6LoWPAN as it connects to the Internet such as congestion. In this paper, we propose a new RPL routing metric called Buffer Occupancy which reduces the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…Some papers call it loss probability [42]. This metric takes into account the total number of lost packets due to buffer overflow and wireless channel loss [39], [44]. Queue length (queue level): this metric shows the average number of packets stored in the nodes' buffer over time [45], [46].…”
Section: Performance Evaluation Metricsmentioning
confidence: 99%
“…Some papers call it loss probability [42]. This metric takes into account the total number of lost packets due to buffer overflow and wireless channel loss [39], [44]. Queue length (queue level): this metric shows the average number of packets stored in the nodes' buffer over time [45], [46].…”
Section: Performance Evaluation Metricsmentioning
confidence: 99%
“…The lower density gives the objective function less options making the difference in performance of mRPL and D-RPL down to 2% only. Higher node density increases the chance of collisions and leads to higher packet loss due to interference and congestion [22].…”
Section: Practical Testingmentioning
confidence: 99%
“…In [22], Al-Kashoash et al proposed a new RPL based objective function called congestion-aware objective function (CA-OF) that works efficiently when congestion occurs. The proposed objective function combines two metrics (buffer occupancy and ETX) and forwards packets to sink node through less congested nodes.…”
Section: Related Workmentioning
confidence: 99%
“…1. The authors in [17], [22], [28], [29] also have demonstrated the problem of "load balancing" or "parent selection" within congestion in the RPL routing protocol. However, even with congestion aware routing metrics and objective functions, sometimes a leaf node can not find a less or non-congested parent and the incoming rate to the parent is higher than its outgoing rate.…”
Section: Network Setup and Problem Formulationmentioning
confidence: 99%